Copyright Law and the Information Profession in Nigeria: Legal Challenges and Opportunities in the Digital Environment - Ebbih, Innocent Onohomhen; Ikpotokin, Omobolanle O. (Communicate: Journal of Library and Information Science, 2025)
The evolving digital landscape has transformed the way information is created, shared, and accessed, presenting both opportunities and legal challenges for information professionals in Nigeria. With the enactment of the Copyright Act, 2022, significant changes have been introduced to Nigeria’s copyright regime, particularly concerning digital rights, fair dealing, and enforcement mechanisms. This paper critically examines the implications of the revised copyright framework for Intellectual Property Lawyers, librarians, archivists, and other information professionals. It explores the tension between copyright protection and access to knowledge, highlighting the ambiguities in law and practice. The paper also draws on international best practices to propose policy and legal reforms that balance the rights of copyright holders with the professional duties of information workers to ensure equitable access to information.